2023
DOI: 10.1126/sciadv.add8946
|View full text |Cite
|
Sign up to set email alerts
|

Convergent abnormalities in striatal gene networks in human cocaine use disorder and mouse cocaine administration models

Abstract: Cocaine use disorder (CUD) is an intractable syndrome, and rising overdose death rates represent a substantial public health crisis that exacts tremendous personal and financial costs on patients and society. Sharp increases in cocaine use drive the urgent need for better mechanistic insight into this chronic relapsing brain disorder that currently lacks effective treatment options. To investigate the transcriptomic changes involved, we conducted RNA sequencing on two striatal brain regions that are heavily im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 76 publications
4
14
0
Order By: Relevance
“…One such regulator is TWIST1, which was down-regulated in withdrawal but up-regulated upon cocaine challenge. Our previous research supports the involvement of TWIST protein family members in the response to cocaine exposure, highlighting the inhibitory role of TWIST2 as an upstream regulator in human CUD ( 23 ). Another identified upstream regulator is BDNF, which is known to influence synaptic plasticity and addictive behaviors in animals ( 72 , 73 , 75 , 76 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One such regulator is TWIST1, which was down-regulated in withdrawal but up-regulated upon cocaine challenge. Our previous research supports the involvement of TWIST protein family members in the response to cocaine exposure, highlighting the inhibitory role of TWIST2 as an upstream regulator in human CUD ( 23 ). Another identified upstream regulator is BDNF, which is known to influence synaptic plasticity and addictive behaviors in animals ( 72 , 73 , 75 , 76 ).…”
Section: Discussionsupporting
confidence: 84%
“…Probing the proteomic landscape—spanning membrane, cytosolic, and nuclear domains—is one approach to understanding the molecular foundations of CUD and one that importantly complements recent efforts at the transcriptomic level ( 23 28 ). The proteomic shifts in addiction-related disorders touch upon a plethora of cellular processes, from synaptic plasticity, neuropeptide dynamics, and intracellular signaling pathways to epigenetic modulation of cocaine-responsive gene expression ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gene ontology for “Biological Processes 2021” and “Molecular Functions 2021” databases were performed in R using the enrichR package with our filtered DEG lists as input (25% fold change (logFC) and p<0.05) 19,28 . Ingenuity Pathway Analysis (IPA; Qiagen) was used to predict upstream regulators associated with DEGs (25% fold change (logFC) and p<0.05) for each experimental condition.…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatic analyses were used to reveal gene expression patterns, biological functions, potential upstream regulators, and co-expression modules of gene networks in an NAc subregion-specific manner across behavioral conditions. To clinically leverage our transcriptomic findings, we integrated the present results with an available transcriptomic dataset of NAc samples from patients with cocaine use disorder (CUD) 19 . Understanding the behavioral and transcriptional correlates of different WD/Ext settings will provide actionable information to better manage relapse triggers and achieve long-term abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…Two epigenome-wide studies using reduced representation bisulfite sequencing (RRBS) in a cohort of N=25 individuals with CUD and N=25 control individuals identified N=145 and N=173 CUD-associated differentially methylated regions (DMRs) in the nucleus accumbens (NAc) 18 and in the caudate nucleus (CN) 19 , respectively. Investigating the same brain regions in a different cohort (N=25 CUD cases, N=20 controls), another study characterized transcriptome-wide gene expression changes and reported on the upregulation of synaptic transmembrane transporter genes while immune processes were downregulated 20 . The largest study in the human PFC investigating CUD-associated transcriptomic changes (N=19 CUD, N=17 controls) identified N=883 nominally significant (p<0.05) differentially expressed genes (DEGs) in neuronal nuclei from the Brodmann Area 46 subregion 21 .…”
Section: Introductionmentioning
confidence: 99%